Inhibition Potential of Extract of Leaves of Sodom Apple in the Corrosion of Mild Steel in 1.0 M H2SO4 (CaJoST, 2024)
Corrosion inhibition of mild steel in 1.0 M sulphuric acid by extract of leaves of Sodom apple has been studied using gravimetric and surface analysis. Varying concentrations (0.5, 1.0, 1.5 and 2.0 g/mL) of the inhibitor in 1.0 M H2SO4 were prepared from residue of an ethanolic extract of the sample and were used for the corrosion inhibition study. The extracts were previously confirmed by Fourier Transform Infrared Spectroscopy and screened for phytochemicals including tannins, saponins, and cardiac glycosides. The results for anticorrosion studies showed that the highest inhibition efficiency of the extract was 89.3% at 1.5 g/mL inhibitor concentration and a temperature of 323 K. Equally, the corrosion rate of the steel was observed to decrease with increase in the concentration of the extract. Scanning electron micrographs also indicated that the extract actually slows down the rate of corrosion of the steel. The study further suggests that the corrosion inhibition mechanism of the extract on steel in 1 M H2SO4 could be modelled using Freundlich isotherm and that the inhibition was by physisorption and formation of multilayers on the steel surface.